Nipah virus (NiV): a ‘new’ addition to the ever changing landscape of infections - James, Sruthi; Banerjee, Indrajit; Sathian, Brijesh; van Teijlingen, Edwin (Nepal Journal of Epidemiology, 2018)
Public Health professionals and researchers always need to be on their toes as the pool of viruses is forever changing. One recent example of this change is the Nipah virus (NiV). This infection is a type of zoonosis, emerging from the family of Paramyxoviridae, genus Henipavirus (RNA virus) and the natural host is Pteropus fruit bat. For Public Health surveillance and multidisciplinary approaches on investigations and therapy and development of vaccines are vital. As with all emerging viruses harmful to humans, an effective system for the detection of infectious diseases as well as for the identification for new causes, risk factors and characteristics in challenged settings is crucial to reduce the disease burden in the population.